2020
DOI: 10.1039/c9nj05489h
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine and amide-ornamented novel nitrogen heterocyclic hybrids: synthesis, biological and molecular docking studies

Abstract: The synthesis of phenothiazine and amide-ornamented nitrogen heterocycles (25–34) has been accomplished utilizing a multi-step synthetic protocol and the structures have been established based on physical and spectral techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Phenothiazine, a fused tricyclic aromatic entity with nitrogen and sulfur heteroatoms in the middle six-membered ring, is one of the important structural units existing in a diverse range of bio-pertinent chemical entities and sensitizers. In continuation of our endeavors on methodology development and the synthesis of heterocyclic molecules, [63,[65][66][67][68][69][70] we initially synthesized phenothiazinylmethylenemalononitrile 4a from its corresponding phenothiazine-based carbaldehyde precursor 2a, synthesized from commercially available 10Hphenothiazine through hexylation followed by condensation and formylation (Vilsmeier-Haack reaction) strategies, and malononitrile with the use of sodium ethoxide in ethanol in order for its cytotoxicity evaluation against pancreatic cancer cells (Figure 8). Further, this chemical entity would act as an efficient intermediate for the development of potent biological agents as well, as various functionalization can be possible around the phenothiazine nucleus and nitrile functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…Phenothiazine, a fused tricyclic aromatic entity with nitrogen and sulfur heteroatoms in the middle six-membered ring, is one of the important structural units existing in a diverse range of bio-pertinent chemical entities and sensitizers. In continuation of our endeavors on methodology development and the synthesis of heterocyclic molecules, [63,[65][66][67][68][69][70] we initially synthesized phenothiazinylmethylenemalononitrile 4a from its corresponding phenothiazine-based carbaldehyde precursor 2a, synthesized from commercially available 10Hphenothiazine through hexylation followed by condensation and formylation (Vilsmeier-Haack reaction) strategies, and malononitrile with the use of sodium ethoxide in ethanol in order for its cytotoxicity evaluation against pancreatic cancer cells (Figure 8). Further, this chemical entity would act as an efficient intermediate for the development of potent biological agents as well, as various functionalization can be possible around the phenothiazine nucleus and nitrile functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this compound demonstrated less toxicity against normal human cells. 250 Additionally, it also indicated G0/G1 phase cell cycle arrest and caused apoptotic activity by caspase 3 activation.…”
Section: Phenothiazine and Azaphenothiazinementioning
confidence: 98%
“…In recent times, Sivaramakarthikeyan et al 250 achieved the synthesis of phenothiazine-amide ornamented nitrogen heterocycles and found that these hybrids have potential cytotoxicity against SW1990 and AsPCl.…”
Section: Phenothiazine and Azaphenothiazinementioning
confidence: 99%
See 2 more Smart Citations